2013
DOI: 10.1108/10595421311319825
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the telecommunication industry in the Sultanate of Oman using Michael Porter's competitive strategy model

Abstract: Purpose -Michael Porter's Five Forces Model provides an ideal mechanism and framework to study the Oman telecommunications industry's competitive structure. The purpose of this paper is to use this model to identify the competitive forces that affect it the most. Design/methodology/approach -This paper is based on empirical research. The data were collected primarily from secondary sources such as published interviews of chief executive officers of the telecommunication companies in Oman, government reports, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 10 publications
2
13
0
1
Order By: Relevance
“…This way the buyer controls their spending making them unpredictable and as a result organizations have to curry out numerous market analysis in order to strategize accordingly. The findings are consistent to those of Rajasekar and Raee (2013) who found out that there was high bargaining power of buyers in Oman.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…This way the buyer controls their spending making them unpredictable and as a result organizations have to curry out numerous market analysis in order to strategize accordingly. The findings are consistent to those of Rajasekar and Raee (2013) who found out that there was high bargaining power of buyers in Oman.…”
Section: Findings and Discussionsupporting
confidence: 92%
“…Policy Directions, Strategies, and Priority Outputs for 2020-2024 resulting from the SWOT Matrix are described in Table 4. components, and substitute products are factors that can threaten the existence of a company engaged in telecommunications [20]. Francis and Martin [14] in their research related to the university's response strategy to the dynamics of changes in government policy, reforms at universities, pressure from stakeholders concluded that universities need to change strategic management that is responsive to change by considering the results of the Porter's five forces model analysis combined with other analytical instruments in order to guarantee the sustainability of higher education institutions.…”
Section: Fig 2 Comparison Of Swot Analysis Between Unimed's Strategmentioning
confidence: 99%
“…The mobile phone connections and subscriptions were introduced in 1996 and by the year 2000, prepaid mobile subscriptions were made offered (Telecommunications Regulatory Authority (TRA, 2004). As per 2009 data, the telecommunication industry in Oman was worth $1.5 billion (Rajasekar and Al Raee, 2013). Currently, the Omani telecommunications service industry is growing at a very fast rate.…”
Section: Introductionmentioning
confidence: 99%